Consumer Protection in India with respect to E-consumers: A step towards Viksit Bharat (Maharaja Surajmal Institute Law Journal, 2024)
The swift expansion of shopping activity within India has resulted in a notable rise  of digital transactions online and puts a spotlight on the importance of ensuring  consumer welfare within the virtual marketplace setting there. This piece delves  into the progression of safeguard measures for consumers within India particularly  concerning those engaging as e buyers. Enacted recently are regulations such as  the Consumer Protection Act of 2019 and the E commerce Rules from 2020 that  aim to fortify consumer rights by putting forth safeguards including setting up  the Central Consumer Protection Authority and outlining provisions, for product  liability. Nevertheless obstacles like unpredictability among negotiating parties,  privacy risks, unjust trading methods and undisclosed expenses continue to exist.  The piece sheds light on the structure overseeing online business activities within  India encompassing statutes such as the Consumer Protection Act and E commerce  Regulations along with other pertinent legal provisions. Furthermore it explores  the significance of complaint resolution processes and advocates for creative  technological remedies that can reconcile the disparity, between technological  advancements and legal structures. The article states that although the existing  legal structure has tackled issues concerning online consumers to some extent;  a stronger and more effective system is required to shield consumers from scams  and unjust business practices, within the online shopping realm.
Keywords: Business; Consumer; Structure; Commerce; Protection